PENERAPAN MODEL PEMBELAJARAN TIPE STAD UNTUKMENINGKATKAN KEMAMPUAN PEDAGOGIK GURU MELALUI SUPERVISI AKADEMIK DI SEKOLAH BINAAN SMA SWASTA DI KOTA MEDAN - Rusli . Siagian (INSPIRATIF : JURNAL PENDIDIKAN MATEMATIKA, 2016)
ABSTRACTThe purpose of this study was to determine the increase in teachers' ability to implement cooperative learning model student team Achievement division through academic supervision in high  schools private school in the city of medan in the academic year 2015/2016 and to k the increased activity of teachers in implementing cooperative learning model student team Achievement division through academic supervision in high  schools private school in the city of medan in the academic year 2015/2016. This study uses school action research approach by using strategies cycle. Research conducted at the target schools which are Advent Air Bersih Private High School, Padamu Negeri private high school,  An-Nizam Private High School, from January to May 2016, in the academic year 2015/2016. The subjects were 61 teachers in target schools Private High School in the city of medan.  This research was conducted through academic supervision by the researchers as a school superintendent. Data collected by the teachers' ability to carry out an assessment rubric STAD cooperative learning and teacher assessment rubric activity. Based on research conducted, it can be concluded that: 1) the ability of teachers to implement STAD cooperative learning model increase through the academic supervision by votes RPP, KBM I, and KBM II in the first cycle in a row 72, 74, and 75 in the category fail to increase in the second cycle in a row 83, 82 and 85 in the category to achieve success.  2) the application of academic supervision shown to increased the activity of teachers in the application of STAD cooperative learning model of the first cycle to the second cycle with eight aspects of the first cycle in the category enough and two aspects in the poor category into all aspects in both categories at the second cycleKeywords: STAD cooperative learning model , Academic Supervision